Incredible but true [videorecording (Blu-Ray)] - Chabat, Alain, 1958-; Drucker, Léa, 1972- (Arrow Video, 2022)
Alain and Marie are a middle-aged bourgeois couple who move to their new house in a quiet suburb. A key feature of their new abode that the estate agent points out to them is a mysterious tunnel in the basement. Little do they realise that it will turn their lives upside down.